Comparision of Optical Filters in Free Space Optical Communication Systems Under Various Weather Conditions - Atabay, S. Eylem; Unverdi, N. Ozlem (IEEE, 2019)
Free Space Optical Communication, FSO, has come into prominence recently as compared to the other optical communication systems. FSO has impressive advantages such as high data rate, wide bandwidth, better security, and robustness to electromagnetic interference, EMI. The performance of the system depends on the factors such as link distance and meteorological conditions. In this study, a reference FSO system which utilizes Bessel, Butterworth, Chebyshev and Gaussian optical filters is implemented in OptiSystem 16.1 simulation software. Effect of meteorological conditions such as clear, hazy and rainy weather are simulated for various link distances, namely 800, 1000 and 1500 meters. The performances of these optical filters according to the above mentioned factors are evaluated by measurement metrics such as BER, Q factor and eye height.
Keywords: Engineering